1981
DOI: 10.1111/j.1464-0597.1981.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐instructional correlates of student ratings: a brief review

Abstract: In many countries, the social pressure for public accountability and an increased awareness of the issues of 'consumerism' have touched even the hallowed halls of higher education, resulting in a greater emphasis on the systematic evaluation of classroom instruction. Although this movement affects people differently at different levels of academia, its results are pervasive. For example, the movement has been accompanied by (1) increasing pressure on, and from, administrators to ensure that evaluation procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…For the full text of this licence, please go to: http://creativecommons.org/licenses/by-nc-nd/2.5/ Research by Morgan and Ogden (1981) highlighted the gender of the students as one of a number of variables which need to be taken into account when evaluating courses. More recently Feldman (1993) in a review of the literature identified 39 articles which investigated the relationship between gender and student evaluations.…”
mentioning
confidence: 99%
“…For the full text of this licence, please go to: http://creativecommons.org/licenses/by-nc-nd/2.5/ Research by Morgan and Ogden (1981) highlighted the gender of the students as one of a number of variables which need to be taken into account when evaluating courses. More recently Feldman (1993) in a review of the literature identified 39 articles which investigated the relationship between gender and student evaluations.…”
mentioning
confidence: 99%